AN ANALYSIS OF MORAL VALUE “THE BOY WHO HARNESSED THE WIND" MOVIE BY CHIWETEL EJIOFOR - ikhsan dwi primadoni (Lingustic, Literature and English Education, 2023)
This research aimed to analyze the types of moral value of “The Boy who Harnessed the Wind”. The objective of this research was to describe moral value based on Linda and Eyre’s theory occured in the movie “The Boy Who Harnessed the Wind”. The method of the research was descriptive qualitative. The technique for collecting the data was library research. The researcher used movie of sources applied in this thesis. The primary source obtained the movie of “The Boy Who Harnessed the Wind movie”. The secondary source obtained from the books or articles related to the theories. In this research, the researcher found some moral values which were found consist of the value of being and the value of giving; the value of being 7 scenes were found and 9 scenes value of giving. The value of being consists of 1 scene of honesty, 2 scenes of courage, 1 scene of peacebility, 2 scenes of self-reliance and potential, and 1 scene of self-discipline and moderation. The value of giving consists of 1 scene of respect, 1 scene of love, 2 scenes of loyalty, 2 scenes of unselfishness, 2 scenes of kindness and friendliness, and 1 scene of justice and mercy. In conclusion, “The Boy Who Harnessed the Wind” movie contains all aspects of moral value. Keywords: Moral Value, Movie, Analysis